Recent progress of elucidating the mechanisms of drug hypersensitivity - Hashizume, Hideo (Asia Pacific Association of Allergy, Asthma and Clinical Immunology, 2012)
Recent technical approaches to investigating drug hypersensitivity have provided a great deal of information to solve the mechanisms that remain poorly understood. First, immunological investigations and in silico analysis have revealed that a novel interaction between T cells and antigen-presenting cells, namely the pharmacological interaction concept, is involved in drug recognition and the hapten theory. Second, progress in immunology has provided a new concept of CD4+ T cell subsets. Th17 cells have proven to be a critical player in acute generalized exanthematous pustulosis. Our recent findings suggest that this subset might contribute to the pathogenesis of Stevens-Johnson syndrome/toxic epidermal necrolysis. Third, alarmins, molecules associated with innate immunity, are also associated with exaggeration and the persistence of severe drug hypersensitivity. The latest innovative techniques are providing a new landscape to examine drug hypersensitivity.